USING PICTURE THERAPY CARDS TO IMPROVE STUDENTS’ VOCABULARIES OF AUTIST CLASS AT SD AGAPE WONOSOBO - Siti Zulaecha; Rochyani Lestiyanawati (CLLiENT (Culture, Literature, Linguistics, and English Teaching), 2023)
English was an international language, so it was not only for common children who had to learn English but children with autism also had to learn English. Learning English did not only involve the structure and vocabulary of the language but also learning to communicate in it. The research aimed to determine the improvement in English vocabulary skills of autistic students by using Picture Therapy Cards as a learning technique in the classroom. The qualitative research followed the type of Classroom Action Research (CAR), conducted at SD AGAPE Wonosobo. In this study, the sample used was an autism class of 8 students. The research followed the Stephen Kemmis and Robin McTaggart model, involving the following procedures: planning, action, observation, and reflection. The research was carried out in two cycles, and data were collected through interviews, questionnaires, observations, and tests. The results of this research showed that: (1) The application of Picture Therapy Cards during learning improved the English vocabulary skills of students with autism. (2) There was a difference in the improvement of vocabulary skills of autistic students before and after using Picture Therapy Cards. This was proven by the increase in the class average score on the final exam produced by autistic students. The class average score in cycle I before taking action on the pre-test was 49.1. The class average cycle II score after the action was 75. The increase in the class average score during the pre-test and post-test was 52,74%. In conclusion, the use of Picture Therapy Cards improved English vocabulary skills in classes of autistic students.